桌上遊戲融入國小二年級「加減法」 學習扶助教學之行動研究 Action Research in the Application of Board Games in Remedial Instruction for Addition and Subtraction Curriculum of Second Graders in Elementary School - 翁鈺婷 Yu-Ting Wong; 詹惠雪 Hui-Hsueh Chan (National Changhua University of Education, 2023)
本研究探討桌遊融入數學「加減法」單元學習扶助教學之實施歷程及學習成效，以國小二年級五位學生為研究對象，採行動研究法，設計「二位數的加減法」、「加減應用」、「加減兩步驟」三個單元課程，分別運用「撲克99」、「你加我減」、「數大為王」三款桌上遊戲，於109年11月至109年12月進行兩循環教學。透過課堂觀察、訪談、學習單、前後測試卷、省思札記等資料，進行綜合分析。本研究主要發現如下：一、依數學概念選擇適合的桌遊可協助學習扶助學生提升能力。二、需適度調整桌遊的難度及遊戲規則，讓學生維持學習的興趣。三、桌遊有助於學習扶助學生加減法數學概念的建立，並能提升基本運算能力。 This study explored the effectiveness of incorporating board games into the teaching of "Addition and Subtraction" unit in second-grade remedial mathematics instruction. Employing the action research method, five second-grade students were selected as the participants, and three unit courses were designed: "Addition and Subtraction of Two-Digit Numbers", "Application of Addition and Subtraction", and "Two Steps of Addition and Subtraction". The teaching was conducted over two cycles from November 2019 to December 2019, using the board games "Poker 99", "You Add and I Subtract", and "The Biggest Number is the King" as instructional aids. Data were collected from classroom observations, interviews, worksheets, pre- and post-test papers, and reflection notes. The analysis results indicate that 1. Choosing an appropriate board game based on mathematical concepts enhances students' mathematics abilities; 2. Adjusting the difficulty and rules of board games helps maintaining students' motivation in learning; 3. Board games facilitate the establishment of mathematical concepts of addition and subtraction, and improve basic computation skills.